Influence of land-use history and ENSO on the flora of the Southern Line Islands - Lauren Nerfa; J. Michael Fay; Allyson Earl; Alan M. Friedlander; Enric Sala; Tamara Ticktin (PLoS ONE, 2026)
Remote tropical islands host unique ecosystems with rare species that have been historically affected by habitat degradation and species introductions, and now by climate change. However, we know little about the current ecological conditions of remote island ecosystems, particularly after the abandonment of commercial land uses. The Southern Line Islands, Kiribati, are among the least studied island groups in the Pacific. These islands have a history of land use, including guano extraction and coconut plantations (1800s to early 1900s), but have no current human uses or habitation. They have been exposed to El Niño Southern Oscillation (ENSO) events, particularly the strong 2015−2016 event. We studied the vegetation of Flint Island, Millennium Atoll, and Vostok Island to assess vegetation succession since the cessation of land-use, and whether they have been impacted by ENSO. Specifically, we drew on field surveys and satellite images from 2009 and 2021, and assessed changes in floristic characteristics between (i) current and historic surveys; (ii) islands with different land-use histories; and (iii) before and after the 2015−2016 ENSO. We found that extant species richness differed from the historic studies, due in large part to the disappearance of some non-native species on Millennium and Flint, and the emergence of some previously undocumented native species across the islands. Species composition differed across islands; Vostok Island has few species compared to Flint or Millennium due to its diminutive size, and remains dominated by Pisonia forest. There were few differences in plant species frequency and composition for the islands between 2009 and 2021, but normalized difference vegetation index (NDVI) values and land-use classification showed some evidence of dry conditions after the 2015−2015 ENSO. We conclude with recommendations for management of non-native species to support regeneration of the native ecosystems of the Southern Line Islands, with implications for other Pacific islands.